Socio-Technological Factors Influencing the Use of GSM in Communication and Sustainable Development in Nigeria - Omiunu, Ojinga Gideon (Bina Nusantara University, 2017)
The study investigates the influence of social and technological problems/factors and the use of GSM in communication towards ensuring sustainable development in Nigeria. The multi-stage sampling technique is used for this study. The local governments are divided into two major strata, and from each stratum, one local government is selected randomly. From the Ibadan-lesscity, Akinyele local government is selected, and from Ibadan urban, it is Ibadan North East. Also, since the population of GSM users are unknown, a convenientsampling technique is deployed to select 200 respondents. The result reveals that although GSM users are satisfied with the reliability of the communication by mobile phones, some problems exist. Those problems are network issues, inability to perceive what the person at the other end is doing, and mistrust and distrust among speakers. Those problems have affected the satisfaction and use of GSM. In addition, some personal, social, and technological factors influence the efficient and nonefficient use of GSM (p < 0:05). As a result, users deploy various strategies to ameliorate these problems. Finally, GSM use among mobile users has a significant effect on users development (p < 0:05), which can bepersonal or communal. It is recommended that telecommunication should upgrade the system to encourage good interpersonal communication among GSM users and also consider some personal and social factors to enhance theefficiency use of GSM that will have sustainable impact on lives.